2019
DOI: 10.1128/aem.02089-18
|View full text |Cite
|
Sign up to set email alerts
|

Periodic and Spatial Spreading of Alkanes and Alcanivorax Bacteria in Deep Waters of the Mariana Trench

Abstract: In the oligotrophic environment of the Mariana Trench, alkanes as carbohydrates are important for the ecosystem, but their spatial and periodic spreading in deep waters has never been reported. Alkane-degrading bacteria such as Alcanivorax spp. are biological signals of the alkane distribution. In the present study, Alcanivorax was abundant in some waters, at depths of up to 6,000 m, in the Mariana Trench. Genomic, transcriptomic, and chemical analyses provide evidence for the presence and activities of Alcani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Moreover, glycolysis was most abundant in surface waters, whereas gluconeogenesis, the glyoxylate shunt and oxidative phosphorylation were more common in >10,000 m waters. Recent studies showed that microorganisms tend to utilize some refractory organic carbon compounds (e.g., alkanes) in the deep-sea zones and labile carbohydrates in surface waters, respectively [ 2 , 63 ]. This indicates that more bacteria exploit labile carbohydrates via glycolysis at the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, glycolysis was most abundant in surface waters, whereas gluconeogenesis, the glyoxylate shunt and oxidative phosphorylation were more common in >10,000 m waters. Recent studies showed that microorganisms tend to utilize some refractory organic carbon compounds (e.g., alkanes) in the deep-sea zones and labile carbohydrates in surface waters, respectively [ 2 , 63 ]. This indicates that more bacteria exploit labile carbohydrates via glycolysis at the surface.…”
Section: Discussionmentioning
confidence: 99%
“…The analyses on the datasets of 16S rRNA gene amplicons from marine samples were described in our previous study [59]. The representative reads of Tenericutes OTUs were recruited for this study.…”
Section: Phylogenetic and Phylogenomic Analysesmentioning
confidence: 99%
“…To examine vertical distribution of the four Bdellovibrionota groups (Fig. 1A) in marine water zones, the 16S rRNA sequences (16S metagenomic Illumina tags, miTags) of Tara ocean (23) and Mariana marine metagenomes (24, 25) were used to calculate relative abundance of Bdellovibrionota groups. Bacteriovoracia and Bdello-group2 were relatively abundant in oceans, compared to the other two groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…16S rRNA sequences of Bdellovibrionota genomes and MAGs were extracted by using rRNA_hmm_fs_wst (v.0) (75) and used to create a 16S rRNA database. The Bdellovibrionota 16S miTags in Tara Ocean (23) and Mariana (24, 69) marine water metagenomes (Table S7) were identified by blastn (v.2.9.0) (-evalue 1e-05) against the 16S rRNA sequence database of Bdellovibrionota. Only the 16S miTags longer than 100bp and >97% identity to a reference in the database were selected for further calculation of their relative abundance in the marine samples.…”
Section: Methodsmentioning
confidence: 99%